A Novel Protocol to Measure Short Sprint Performance. (2016) - Healy, R.; Norris, M.; Kenny, I.C.; Harrison, A.J.
Abstract: This study assessed the validity of a novel protocol in the measurement of 5 and 10 m sprint time from standing and block starts. Sprint time was assessed using high speed video timing and a novel method which incorporated dual beam photocells synchronized with an optical measuring system. Team sport athletes and sprinters completed 10 m sprints from standing and block starts with both methods measuring sprint time concurrently. No significant differences were found between methods (p > 0.05) with a negligible mean bias (< 0.01 s). These results suggest that the novel method can accurately measure short sprint performance.